Syndemics of Severity and Frequency of Elder Abuse: A Cross-Sectional Study in Mexican Older Females - Vilar-Compte, Mireya; Gaitán-Rossi, Pablo (Frontiers in Psychiatry, 2018)
Background: Elder abuse is a common phenomenon with important effects on the health and wellbeing of older adults. There are important gaps in elder abuse measurement, as it is usually reported as the absence or presence of elder abuse, disregarding its severity and frequency. Objectives: Identify different ways of measuring severity and frequency of elder abuse and assess whether different experiences of severity and frequency suggest syndemic relationships. Methods: Through a sample of 534 non-institutionalized Mexican older women living, we assess how severity (i.e. number of abusive experiences and number of types of abuses) and frequency (i.e. if abusive experiences had happened few or many times) correlated among them. For each of these measures we estimated a multinomial model assessing associations with social support, functional impairments, socioeconomic status, food insecurity, depression and comorbidities, while controlling for key socio-demographic variables. Results: 30.5% of the older women reported psychological abuse, 8.2% financial exploitation, 5.1% caregiver neglect, 3.5% physical abuse, and 1.2% sexual abuse. In terms of frequency, 77.8% self-reported having never been abused or only once in the last 12 months, whereas 13.1% reported abusive experiences repeating few times, and 9.9% repeating many times. In terms of severity, 66.7% of the older women had not been abused, 22.3% had suffered one type of abuse, and 11.1 % two or more. Similarly, 15.0% reported one abusive experience, 8.1% two, and 10.3% three or more abusive events during the last 12 months. Severity measures showed similar associations: social support and high socioeconomic level as protective factors among those with less severe abuse, whereas increased depression, food insecurity and functional impairments were associated with more severe experiences of elder abuse. Frequency followed a different pattern, depressive symptoms were significantly associated with those with few experiences (compared to those with none or once), while functional impairments were associated with many experiences of elder abuse. Conclusions: It is relevant to assess elder abuse through its severity and frequency as inter-individual variability and the complexity of the experience shows different determinants suggesting a syndemic approach. This has important clinical and policy implications.